Where are all the new antibiotics? The new antibiotic paradox - JM Conly; BL Johnston (Canadian Journal of Infectious Diseases and Medical Microbiology)
At the beginning of the 20th century, illnesses caused by infectious agents ranked among the most common causes of death in North America and, indeed, worldwide. By the middle of the century, dramatic advances in the diagnosis, management and prevention of infectious diseases had occurred, and hopes were raised that many infectious diseases would be eliminated by the end of the 20th century. Much of this success in the management of infectious diseases was related to a continuous new armamentarium of antibiotics. The discovery of penicillin by Fleming in 1928 followed by the discovery and clinical use of sulphonamides in the 1930s heralded the age of modern antibiotherapy (1,2). Penicillin came into widespread use during the early 1940s. By the 1950s, the 'golden era' of antibiotic development and use was well underway, and multiple new classes of antibiotics were introduced over the next two decades (Table 1) (3).